Nonlinear relationship between blood urea nitrogen to albumin ratio and mortality risk in older patients with cerebrovascular and cardiovascular diseases: An NHANES analysis - Li Li; Chengbo Li; Jiang Zhu (PLoS ONE, 2025)
Background The blood urea nitrogen to albumin ratio (BAR) has emerged as a potential prognostic biomarker in elderly patients with cardiovascular and cerebrovascular diseases (CVDs). This study investigates the association between BAR and all-cause as well as cardiac mortality in this population. Methods We analyzed data from 4,113 elderly CVDs patients derived from the National Health and Nutrition Examination Survey (NHANES), with a mean follow-up of 82.4 months. Participants were categorized into three BAR groups: T1 (<3.55), T2 (3.55–5.00), and T3 (≥5.00). Weighted multivariable Cox regression assessed the association between BAR and all-cause mortality. The Fine and Gray competing risks model evaluated cardiac mortality, accounting for competing events. Hazard ratios (HRs) were calculated for continuous and categorical BAR. Subgroup, threshold effect, and sensitivity analyses were performed to confirm the robustness and explore nonlinear relationships. Results During follow-up, 2,178 all-cause and 752 cardiac deaths occurred. Continuous BAR was significantly associated with increased all-cause mortality (HR = 1.10, 95% CI: 1.07–1.13, p < 0.001). Compared to T1, the highest BAR group (T3) showed elevated all-cause mortality risk (HR = 1.33, 95% CI: 1.16–1.53, p < 0.001). Each unit increase in BAR corresponded to a 9% increase in all-cause mortality and a 14% increase in cardiac mortality. Threshold analysis revealed a nonlinear association with increased risk above specific BAR levels. Subgroup and sensitivity analyses further validated these findings. Conclusion BAR is a significant and independent predictor of all-cause and cardiac mortality in elderly patients with CVDs. Incorporation of BAR into clinical risk assessment may help improve identification of high-risk patients and support targeted interventions.